Efficiency of using of the mineralized malts composition for the enhancement of food products by micronutrients - Bashta (Sheremet), Alla; Ivchuk, Nadiya; Bashta, Oleksandr (My University, 2019)
In the whole world there is a deficit of micronutrients, which leads to the development of various diseases. The purpose of research is to obtain and investigate the composition of malts with high content of deficient micronutrients and enrichment with selected raw materials the rye-wheat bread.The subject of research is malt of cereals (maize and oat), salts of chromium and zinc, mineralized malt, rye-wheat bread enriched with the composition of mineralized malts. X-ray fluorescence analysis was used to determine the mineral composition of grain and malt and stripping voltammetry method to determine the zinc content.The addition of such mineralized raw materials to food products formula will enrich them with biologically active substances, giving them functional properties.
Keywords: maize; oat; malt; zinc; chromium; кукурудза; овес; солод; цинк; хром; кафедра технології оздоровчих продуктів